Pengaruh Penggunaan Serat Hybrid terhadap Kekuatan Impak - Musthofa, Wildan; Dewi Anjani, Ratna Dewi Anjani (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Natural fibers have weaknesses, including lower mechanical properties than synthetic fibers, and higher water absorption. The impact test is a mechanical test which aims to measure the resistance of materials to shock loads. The aim of this research is to determine the effect of using hybrid fibers on impact strength. This research uses impact testing with the Charpy method. Results: The highest breaking strength value was found in the volume fraction of hemp fiber and 15% synthetic fiber of 3.98885 J, and the highest impact value was found in the volume fraction of 15% hemp fiber: 5% synthetic fiber of 31.53 KJ/m². The conclusion from the tests that have been carried out can be concluded that the more fibers used, the higher the fracture strength and impact value.